FINANCIAL PERFORMANCE IN THE CROP PRODUCTION SECTOR IN THE ERA OF DIGITAL TRANSFORMATION - Dimitrina STOYANCHEVA; Dora DONCHEVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper analyses the financial performance of crop production enterprises related to the costs associated with their innovation activity. We aim to determine influencing factors related to the digital transformation process, on the one hand, and on the other, explore the change in the economic performance of enterprises. For this purpose, we trace out enterprises' intangible assets and financial performance indicators. The study is based on a sample of enterprises, classified according to whether they disclose intangible assets in balance sheets. We use panel data collected on financial results, income, expenses, liabilities, and assets for five years. Both the Probit model and Fixed effects model are applied in an attempt to deepen the analysis. The results show that enterprises spend a negligibly small share of their revenue on innovation activities.Larger and more innovative crop farms with higher labour productivity have better financial performance. However, we found out that the higher value of return on assets does not affect enterprises' innovation decisions.